A Brief Screening Tool for Opioid Use Disorder: EMPOWER Study Expert Consensus Protocol - You, Dokyoung S.; Mardian, Aram S.; Darnall, Beth D.; Chen, Chwen-Yuen A.; De Bruyne, Korina; Flood, Pamela D.; Kao, Ming-Chih; Karnik, Anita D.; McNeely, Jennifer; Porter, Joel G.; Schwartz, Robert P.; Stieg, Richard L.; et al. (Frontiers in Medicine, 2021)
Growing concerns about the safety of long-term opioid therapy and its uncertain efficacy for non-cancer pain have led to relatively rapid opioid deprescribing in chronic pain patients who have been taking opioid for years. To date, empirically supported processes for safe and effective opioid tapering are lacking. Opioid tapering programs have shown high rates of dropouts and increases in patient distress and suicidal ideation. Therefore, safe strategies for opioid deprescribing that are more likely to succeed are urgently needed. In response to this demand, the EMPOWER study has been launched to examine the effectiveness of behavioral medicine strategies within the context of patient-centered opioid tapering in outpatient settings (https://empower.stanford.edu/). The EMPOWER protocol requires an efficient process for ensuring that collaborative opioid tapering would be offered to the most appropriate patients while identifying patients who should be offered alternate treatment pathways. As a first step, clinicians need a screening tool to identify patients with Opioid Use Disorder (OUD) and to assess for OUD severity. Because such a tool is not available, the study team composed of eight chronic pain and/or addiction experts has extended a validated screening instrument to develop a brief and novel consensus screening tool to identify OUD and assess for OUD severity for treatment stratification. Our screening tool has the potential to assist busy outpatient clinicians to assess OUD among patients receiving long-term opioid therapy for chronic pain.